Preparation, intestinal segment stability, and mucoadhesion properties of novel thymopentin-loaded chitosan derivatives coated with poly (n-butyl) cyanoacrylate nanoparticles - Xu Y (Dove Medical Press, 2019)
Ying Xu,1 Shengzhe Lu,1 Qi Liu,2 Yun Hong,3 Bohui Xu,4 Qineng Ping,5 Xuefeng Jin,5 Yan Shen,5 Thomas J Webster,6 Yuefeng Rao3,7 1Department of Pharmaceutics, School of Pharmacy, Jiangsu University, Zhenjiang, 212013, China; 2Department of Dermatology, Johns Hopkins University School of Medicine, Baltimore, MD 21231, USA; 3Department of Pharmacy, School of Medicine, The First Affiliated Hospital, Zhejiang University, Hangzhou 310003, China; 4Department of Pharmacy, School of Pharmacy, Nantong University, Nantong 226001, China; 5Department of Pharmaceutics, School of Pharmacy, China Pharmaceutical University, Nanjing 210009, China; 6Department of Chemical Engineering, Northeastern University, Boston, MA 02115, USA; 7Department of Pharmaceutics, College of Pharmaceutical Sciences, Zhejiang University, Hangzhou 310058, China Background: In order to develop a promising carrier for the oral delivery of proteins and peptide drugs, a novel bioadhesive nanocarrier of chitosan (CTS) derivatives coated with poly (n-butyl) cyanoacrylate nanoparticles (PBCA-NPs) was prepared in this study.Methods: Three different thymopentin (TP5)-loaded nanoparticles were prepared in the present study. TP5-PBCA-NPs were developed by modifying an emulsion polymerization method, and CTS and chitosan–glutathione (CG) derivative-coated PBCA nanoparticles were obtained from the electrostatic interactions between CTS or CG with negatively charged PBCA nanoparticles.Results: The particle sizes of TP5-PBCA-NPs, TP5-CTS-PBCA-NPs, and TP5-CG-PBCA-NPs were 212.3±6.9, 274.6±8.2, and 310.4±7.5 nm, respectively, while the respective zeta potentials were –22.6±0.76, 23.3±1.2, and 34.6±1.6 mV with encapsulation efficiencies of 79.37%±2.15%, 74.21%±2.13%, and 72.65%±1.48%, respectively. An everted intestinal ring method indicated that drug stability was remarkably improved after incorporation into the nanoparticles, especially the CG-coated nanoparticles. The mucus layer retention rates for CTS- and CG-coated nanoparticles were 1.43 and 1.83 times that of the uncoated nanoparticles, respectively, using ex vivo mucosa. The in vivo mucoadhesion study illustrated that the transfer of uncoated PBCA-NPs from the stomach to the intestine was faster than that of CTS-PBCA-NPs and CG-PBCA-NPs, while the CG-PBCA-NPs presented the best intestinal retentive characteristic.Conclusion: In summary, this study demonstrated the feasibility and benefit of orally delivering peptide drugs using novel CTS derivative-coated nanoparticles with optimal stability and bioadhesive properties. Keywords: chitosan derivatives, PBCA nanoparticles, thymopentin, stability, bioadhesive